Effectivity of Services In South Tangerang City Public Services Mall - Riyakudu Maulana; Bahrullah Akbar; Baharudin Tahir (Journal Of Social Science (JoSS), 2024)
The establishment of the South Tangerang City Public Service Mall is a follow-up to the Regulation of the Minister of Administrative Reform and Bureaucratic Reform of the Republic of Indonesia Number 23 of 2017 Article 1. This research aims to find out how the effectiveness of services and efforts made to improve the effectiveness of services at the South Tangerang City Public Service Mall. This research uses a qualitative method with a descriptive approach with primary and secondary data sources. Data collection techniques were carried out using interviews, observation and documentation, Data analysis techniques used were data reduction, data presentation and conclusion drawing. The results show that the effectiveness of services at the Public Service Mall of South Tangerang City is quite good. First, service procedures are considered effective because they are easy for the community to understand. Second, the service completion time is quite effective thanks to the service provider's efforts to complete it on time. Third, service fees are in accordance with government regulations and are affordable. Fourth, the facilities and infrastructure in this mall are comfortable and complete, supported by good information technology. Fifth, employees have competence with a friendly and informative attitude. Finally, service products are in accordance with the provisions and the public is satisfied with the services received. The conclusion of this study shows that services at the Public Service Mall of South Tangerang City are effective, with clear procedures, appropriate completion time, affordable costs, and good facilities and infrastructure.